CORPORATE SOCIAL RESPONSIBILITY IN THE SOUTH AFRICAN RETAIL SECTOR: ARE EMPLOYEES AWARE OF WHAT THEIR EMPLOYERS ARE DOING? - Martha E. Theron; Michael C. Cant; Johannes A. Wiid (Economic Review)
Corporate social responsibility (CSR), which is the adoption of responsible business practices concerning economic, environmental, and social CSR, is an important topic among marketers aiming to develop market value with various stakeholder groups, including employees. Previous research is limited to developed market economies and has focused mainly on external stakeholder groups. This study explored South African retail employees’ awareness of their organizations’ CSR initiatives. The sample size was 229 South African retail employees, from lower-level employees up to middle and senior management. The study made use of a computer-aided self-administered survey, distributed via LinkedIn. The results indicated that lower-level employees are less aware of economic, environmental, and social CSR initiatives implemented by their organizations than those in middle and senior management, but that there was no significant difference between middle and senior managements’ levels of awareness of their organizations’ CSR initiatives. The results also indicated that employees have higher levels of awareness when it comes to internal economic CSR, external economic CSR, and external social CSR, as opposed to internal environmental CSR, external environmental CSR, and internal social CSR initiatives. The findings of the study can assist organizations to customize internal CSR communication strategies.